The parallel complexities of the K-medians related problems - Sirion Vittayakorn (2018)
K -medians is a well-known clustering algorithm in data mining literature. This paper describes three decision problems related to k-medians. These problems are called MEDIANS REPLACEMENT IN k-MEDIANS, MEDIAN DETERMINATION, and TITERATIONS k-MEDIANS problems. We show that these problems are in NC, each has a (logn)O(1) parallel time algorithm on an EREW PRAM model using nO(1) processors, and the result in each case is the strongest possible.1 ©2008 IEEE.